External Contextual Factors and Teacher Turnover: The Case of Michigan High Schools - Minor, Elizabeth Covay; Saw, Guan K; Frank, Kenneth A; Schneider, Barbara; Torphy, Kaitlin T (Teachers College record (1970), 2019)
Background/Context: All organizations face turnover in their workforce; however, in schools high turnover can interfere with the effectiveness and efficiency of the school. While past research has examined school-related factors linked to teacher turnover, few studies have examined how external contextual factors are related to teacher turnover. This study examines the role of two external contextual factors in teacher turnover: economic downturns and changes in state curricular policy (the Michigan Merit Curriculum [MMC]). Purpose/Objective/Research Question/Focus of Study: This study asks the extent to which the economic crisis of 2009 and the implementation of the MMC are related to school-level teacher turnover rates and whether those relationships vary by school locale and within the school year. Population/Participants/Subjects: The data include full-time high school teachers in the state of Michigan aggregated to the school level. Research Design: Using eight years of statewide longitudinal data from Michigan, the study employs school fixed effects models to account for possible differences in unobservable school characteristics that are constant over time and may be related to teacher turnover. The study examines teacher turnover at both the mid-year and the end of the year as teachers leave schools at various points during the school year. Additionally, this study considers how turnover is experience differentially by urbanicity. Findings/Results: Between 3.2% and 15.5% of teachers left their school over the eight-year period. The rates of turnover varied by the time of the school year with more teachers leaving at the end of the year than during mid-year. There was a significant increase in teacher turnover rates around the announcement of the MMC as well as the economic downturn. While all locations were impacted by the announcement of the MMC, the largest amount of turnover occurred in urban areas and the lowest for suburban areas. In terms of the economic downturn, towns were impacted the most, followed by rural and suburban schools. Urban areas did not see a significant increase in teacher turnover related to the recession. Conclusions/Recommendations: The authors conclude that external contextual factors are related to increases in teacher turnover independent of each other. How these factors relate to teacher turnover does depend on school locale. While this study was based in Michigan, all states have their own policy and economic pressures to consider in related to school-level decision making and teacher turnover.